Asian water development outlook 2016 description of methodology and data. (Asian water development outlook., 2017)
It provides background information and explanatory notes on the approach taken, assumptions made, and data used. The methodology itself has been developed by the Asian Development Bank (ADB) in cooperation with reputed scientific institutes who have co-authored the individual reports for each of the five key dimensions of water security. These five reports are integrated into this methodology report. This study was supported by ADB Water Financing Partnership Facility.